Importance of User Studies for Information Retrieval: A Case Study of Assam Agricultural University, Jorhat - Gogoi, Nitumika; Kanjilal, Uma (Journal of Agricultural Extension Management, 2021)
User studies over the years have attempted to explain the information use phenomena, understand and predict information use behavior and improve the information search results by manipulating essential conditions. Librarians are exhorted to develop traits in identifying the distinct groups of users along with their information-seeking habits, sources, and needs. These, in turn, facilitate the successful evaluation of search results in Information Retrieval. The present user study on a sample of 184 users is highlighted as one of the essential tasks that lead to searchoriented query collection from a heterogeneous group of users in the Assam Agricultural University and consider the specific databases for the Information Retrieval process. The users’ satisfaction level can judge the attitudinal approach to information search after retrieving information relevant to the queries submitted by the users